Nutrition Label Usage: An Empirical Study of Consumer Response in India - Paul, Reeva; Bedi, Monica (Indian Journal of Marketing, 2014)
Purpose: Indian consumers are in the process of changing their consumption/buying behaviour, especially with respect to food items. The present study attempts to explore the Indian consumers' level of awareness and usage of information given on food product labels. The research also aims to understand the association of demographic differences with regard to food label usage. Moreover, it intends to identify the specific nutritive and non-nutritive information, and food attributes that consumers seek from food labels. Design/Methodology/Approach: The data was collected using a structured questionnaire-based survey. A total of 250 respondents were considered for the study. Friedman's ANOVA, Descriptive statistics, and Chi-square test were used to analyze the data. Findings: The results indicated that Indian consumers, like consumers in other countries, are reading nutrition labels and that these labels influence their purchase decisions. The research also indicated that quality and nutrition are the primary attributes which consumers seek from food products. Fat, energy, and the amount of cholesterol in food products were found to be the most frequently sought nutritional information, while environment related information was rarely pursued. Income level, education, and gender play a role in the usage of nutritional labels by the consumers. Consumers seek further simplification and standardization of food labels. Originality/Value: The outcomes of the study will help Indian policy makers and food companies to understand the complexity of issues involved in nutrient labelling, and design strategies to maximize benefits from resources spent on food labelling.